WOMEN'S RESISTANCE IN THE NOVEL A THOUSAND SPLENDID SUNS: A MIDDLE EASTERN STUDY FROM THE ISLAMIC FEMINISM PERSPECTIVE - Aiman Aiman; Roma Ulinnuha; Sarwanto Sarwanto (CMES (Center of Middle Eastern Studies), 2022)
This study examines women's resistance in the novel A Thousand Splendid Suns by Khaled Hosseini. The narrative of resistance was caused by women's rebellion against the culture restricting women's freedom in Afghanistan. The object of the study addressed in this novel is the life of Afghan women living in the confines of men and also patriarchal culture and struggle for freedom and escape from patriarchal culture. This study used a feminist approach conceptualized by Barlas feminism about gender equality between men and women. Data analysis involved several stages: data reduction, presentation, and concluding. The result revealed Afghan women's resistance to patriarchal culture in Afghanistan, a form of the cultural revolution in the novel A Thousand Splendid Suns analyzed using Barlas's feminist perspective.